Microstructure and flexural strength of C/HfC-ZrC-SiC composites prepared by reactive melt infiltration method. Issue 5 (May 2023) - Kou, Sijie; Ma, Jingchao; Ma, Yujie; Liu, Yinghao; Luan, Chenghua; Yang, Shaobo; Fan, Shangwu; Deng, Juanli; Wang, Peng
Abstract: C/HfC-ZrC-SiC composites were fabricated via reactive melt infiltration (RMI) of the mixed HfSi2 and ZrSi2 alloys. The microstructure, infiltration behavior of the hybrid silicide alloys infiltrating C/C composites, and flexural strength of C/HfC-ZrC-SiC composites was studied. Inside composites, there were more Hf-rich (Hf, Zr)C phases distributed in the exterior region, while more SiC and Zr-rich (Zr, Hf)Si2 in the interior region. There was compositional segregation in (Hf, Zr)C, with the HfC content decreasing from the exterior region to interior region. The RMI process was performed at different temperatures to investigate the structural evolution, and a model for the reactive melt infiltration of the mixed HfSi2 and ZrSi2 alloys into C/C composites was established. Compared with C/HfC-SiC and C/ZrC-SiC prepared by same process, C/HfC-ZrC-SiC had the highest flexural strength of 247Mpa and 213Mpa after oxidation at 1200 ℃ for 15 min. Both the unoxidized and oxidized samples presented a pseudo-plastic fracture behavior.